Interdisciplinary consensus on management of premenstrual disorders in switzerland - Petra Stute; Christine Bodmer; Ulrike Ehlert; Roger Eltbogen; Ankica Ging; Isabelle Streuli; Michael von Wolff (Publishing House TRILIST, 2019)
Premenstrual disorders (PMD) can affect women throughout their entire reproductive years. In 2016, an interdisciplinary expert meeting of general gynecologists, gynecological endocrinologists, psychiatrists and psychologists from Switzerland was held to provide an interdisciplinary algorithm on PMD management taking reproductive stages into account. Approximately 30-40% of women report premenstrual syndrome symptoms that require treatment, while 3-8% of women during their reproductive years suffer from PMDD. The core PMD can be subdivided into predominantly somatic symptoms, predominantly psychological symptoms or mixed somatic and psychological symptoms. The most frequent psychological symptoms are mood swings, irritability, anxiety and depression. The Swiss algorithm for PMD management seeks to incorporate the structural level of medical care (primary/secondary care) as well as varying content levels (diagnostics, treatment) depending on the reproductive stage of a woman (reproductive phase, menopausal transition). Primary clinical diagnostics (personal history, prospective symptom assessment) should be performed by the primary PMD care provider. If first- and second-line treatment is not successful, the patient should be refered to a secondary PMD care provider, preferably to a gynecological endocrinologist. A psychiatrist is the preferred secondary PMD care provider if a woman presents with variant PMD with psychiatric co-morbidity. Clinical diagnostics will then be completed by a serum laboratory work-up and eventually Treatment options include cognitive behavioral therapy, alternative therapy, antidepressants, ovulation suppression and diuretics. Treatment choice depends on prevalent PMD symptoms, (reproductive) age, family planning, cardiovascular risk factors, comorbidities, comedication and the woman's preference. Regular follow-ups are mandatory. In Switzerland, except for chasteberry (Vitex agnus-castus L.) and progesterone none of the following therapeutic options is approved for PMD treatment.